Selection of the cutoff value of the tuberculin skin test for diagnosing students who need preventive treatment: A school-based cross-sectional study - Lu, Peng; Ding, Xiaoyan; Sun, Jiansheng; Wang, Rong; Liu, Jiasong; Liu, Qiao; Zhu, Limei; Lu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: School tuberculosis outbreaks are common in China. This study aimed to introduce and evaluate a new screening process to help control outbreaks. Methods: Screening information of students in three school tuberculosis outbreaks was collected. QuantiFERON-TB gold in-tube (QFT) results were used as the conference standard to determine the cut-off value of tuberculin skin test (TST) for diagnosing students who needed to have preventive medication. Results: A total of 1,232 students and teachers coming from three different schools which all had more than three student tuberculosis patients were included in this study. In total, 308 (25.0%) students had an induration diameter ≥10mm; among students in a different class with the index case the infection rate was 24.4% (264/1084), which was lower than it among students in a same class (29.7%)(P=0.157); Students in the same class as the index tuberculosis case had a much higher QFT positivity compared to those in a different class (58.1% versus 7.7%, P<0.0001). Diagnostic agreement between TST≥10mm and QFT was 36.6%. The diagnostic value reached highest when the induration diameter of the TST was 9mm or above, with a sensitivity and specificity 94.1%(95%CI:89.4-97.1%) and 27.6%(95%CI:24.9-30.4%), respectively. The area under the curve (AUC) was 0.664 (95%CI: 0.637, 0.690, P<0.0001). Conclusion: In school tuberculosis outbreaks, if there are three or more student tuberculosis cases in a class or the TST moderate or strong positive rate is much higher than the normal range in the region, attention should be paid to the moderately positive TST. IGRAs were recommended to be conducted followed by TST on the day of reading results especially among students sharing the same class with the index case. In resource-poor areas lacking IGRAs, the induration diameter of TST can be appropriately reduced from 15mm to 9 mm to enhance the sensitivity of TST.